Mobile Website design about the effect of watching Mukbang / Angela Merici - Merici, Angela (2022)
To educate and encourage late teens to know what and understand about the effects of watching mukbang through a fun and simple interactive website. Mukbang is known to have various positive and negative effect. A study shown that mukbang is one of the factor that changes viewer's behaviour to unhealthy diets. The lack of interactive and fun media about the subject leads to a minimal understanding of its effects to health.